A High Level of Knowledge Increases The Positive Attitude of Nurses Regarding Covid-19 - Tri Gunarti; Budi Hartoyo; Heru Noor Ramadhan; Wahyuni Ika Putranti; Amin Husni; Retnaningsih Retnaningsih (Media Keperawatan Indonesia, 2021)
During the Covid-19 patients’ treatment process in the hospital, nurses play an important role in preventing the Covid-19 outbreak through proper care and prevention procedures because nurses are in direct contact with Covid-19 patients. This study aimed to produce an analysis of nurses’ level of knowledge and attitudes regarding Covid-19 in the Covid-19 isolation ward of Dr Kariadi Hospital Semarang. This is a descriptive correlation study with a cross-sectional design. The study was conducted on 81 nurses who had or are currently taking care of Covid-19 patients in the isolation ward of Dr Kariadi Hospital Semarang by consecutive sampling. The data were analyzed by the Spearman Rho test. The results of the study showed that 81 nurses (100%) had a high level of knowledge regarding Covid-19 and had good attitudes towards Covid-19 prevention. The result showed a strong relationship between the level of knowledge and attitudes regarding Covid-19 with a positive correlation (r = 0.617). The study result concluded that the higher the level of knowledge, the better the attitude of nurses regarding Covid-19